PEMANFAATAN DAUN MUDA JAMBU BIJI SEBAGAI MASKER KECANTIKAN ALAMI DI DESA KABARON KECAMATAN TULANGAN - SITI NURIYATIN; Dew Sukriyah; Fitri Ningrum Setiawati (JURNAL PADI (Pengabdian mAsyarakat Dosen Indonesia), 2022)
This study was carried out in Kebaron Village Kecamatan Tulangan by the Mathematics Education Study Program. This study aims to show the public how to use young guava leaves as a beauty mask. Guava is an icon of Kebaron Village. The results of this study are increasing the knowledge and skills of the Kebaron village community in utilizing guava leaves. The community responded very well to this activity. Knowledge about processing guava leaves into masks can be continued through collaboration with the Kebaron Village government. This cooperation in processing guava leaves can be used as one of the superior products of Kebaron Village.